Analysis Students' Perception of Using Mobile Assisted Language Learning (MALL) in Reading Class - Andi Mohammad Hardyansyah (Institut Agama Islam Negeri Palopo, 2021)
This study aims to determine students' perceptions of the use of MALL in the reading class on their learning development using mobile phones as a distance learning medium, especially in the current conditions faced by students such as the corona virus which is to overcome this to maintain the quality of student education or education. lecturers must take advantage of MALL, it aims to create an innovative and creative learning environment with an integrated learning system based on faith and piety, as well as science and technology. This study uses descriptive qualitative research. This research was carried out in the second semester students of the English Department at the University of Muhammadiyah Makassar. sample is 20 studentsThe findings of this study indicate that the use of MALL in the learning process in the reading class is quite helpful for them, this can be seen from the scale obtained by students based on the results of the Guttman scale analysis, the results of 66% according to the interpretation table are in the range of 0.51 – 0.99, so it can be concluded It is said that the perception of students who use MALL in the reading class is close to appropriate.